Environmental, oceanographic and fisheries strategy time series (2000-2019) for demersal species in the Brazilian Meridional Margin - José Angel Alvarez Perez; Rodrigo Sant extquotesingleAna (PANGAEA, 2022)
The extquotesingleMean Temperature of Catch (MTC) extquotesingle was estimated for each year of the time series, as proposed by Cheung et al. (2013). This variable is expressed in degrees Celsius. extquotesingleSea Bottom Temperature (SBT) extquotesingle was derived from estimates provided by the high-resolution ocean general circulation INALT20 model (Schwarzkopf et al., 2019) for the study period (2000-2019) and was calculated by averaging the temperatures over 0.25° x 0.25° grid cells of the BMM and a water column up to 50 m above the seafloor. This variable is expressed is degrees Celsius. extquotesingleAnnual volume transports of the Brazil-Malvinas confluence (BCt) extquotesingle was extracted and compiled from Artana et al. (2019). This index was estimated for the period between 2000 and 2017. More detailed information about this index can be accessed in Artana et al. (2019). This variable expressed in Sverdrups (Sv). extquotesingleSimpson diversity index (Dm) extquotesingle express the diversity of demersal fishing métiers (i.e. combination of target species, gear, and time of the year) operating each year of the time series, as determined by a process of classification of individual fishing trips. Catches of each métier operating during each year of time series summed and used to calculate Dm using the Simpson species diversity index formulation.
In: Perez, JAA; Sant extquotesingleAna, R (2022): Time series of catch composition, mean catch temperature and thermal preference of demersal species in the Brazilian Meridional Margin (2000-2019) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.946402